Global debates, local dilemmas : sex-selective abortion in contemporary Viet Nam - Hang, Tran Minh (Vietnam (Series), 2018)
The practice of sex-selective abortion is on the rise globally, stirring debates about gender inequality, medical ethics and reproductive autonomy. This book is the first ethnography to document practices of sex selection in Viet Nam. It shows how and why abortions are used to select the sex of children and how Vietnamese individuals and health professionals are implicated in this illicit and controversial practice. Telling the stories of women who have undergone sex-selective abortions, it traces their passage through sex determination and abortion decision-making phases, and investigates their experiences during and after their sex-selective abortions. It describes the turmoil experienced by individuals who undergo such abortions and explores their interactions with the spectrum of social actors and health institutions that facilitate practices of sex selection.